2021
DOI: 10.1080/03003930.2021.1944857
|View full text |Cite
|
Sign up to set email alerts
|

What happens when municipalities run corporations? Empirical evidence from 290 Swedish municipalities

Abstract: Local governments are increasingly relying on municipally owned corporations (MOCs) to provide public services. Some describe this development as a rational response to austerity challenges and emphasise the cost-efficiency of MOCs ('the optimistic view'). Others identify complications and associate MOCs with weak supervision, lack of accountability, and corruption risks ('the sceptical view'). Hitherto, no studies have analysed these opposing claims on MOCs in the one and same inquiry. We address this gap by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…Constituting only 10.5% of the 573 identified antecedents, scholars have primarily focused on community characteristics, comprising about 90.0% of the environmental antecedents (refer to Table 5 and Appendix 1). Generally, the empirical results indicate a mixed and inconsistent effect of community characteristics on citizen satisfaction, suggesting that the impacts of environmental factors may be highly context-specific (Amirkhanyan et al, 2014; Bergh et al, 2022; Brown, 2007; Drew & Dollery, 2016; Van Ryzin, 2004). For instance, concerning the population size, Drew and Dollery's (2016) study found an insignificant impact in the context of Australia, whereas Bergh et al (2022) observed that a larger population increases the level of citizen satisfaction in the Sweden setting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Constituting only 10.5% of the 573 identified antecedents, scholars have primarily focused on community characteristics, comprising about 90.0% of the environmental antecedents (refer to Table 5 and Appendix 1). Generally, the empirical results indicate a mixed and inconsistent effect of community characteristics on citizen satisfaction, suggesting that the impacts of environmental factors may be highly context-specific (Amirkhanyan et al, 2014; Bergh et al, 2022; Brown, 2007; Drew & Dollery, 2016; Van Ryzin, 2004). For instance, concerning the population size, Drew and Dollery's (2016) study found an insignificant impact in the context of Australia, whereas Bergh et al (2022) observed that a larger population increases the level of citizen satisfaction in the Sweden setting.…”
Section: Resultsmentioning
confidence: 99%
“…0%) Contract characteristics(Amirkhanyan et al, 2014) Ownership(Bergh et al, 2022;Carvalho & Brito, 2012;De Vries & Van der Hooft-Van der Zijl, 2003;Hodgkinson et al, 2017;Kisida & Wolf, 2015) (continued)…”
mentioning
confidence: 99%
“…First, the lack of data meant that our sample did not include other organizations providing public services at the municipal level, such as municipally owned companies (MOCs). This is important because municipalities increasingly rely on MOCs to provide public services (Bergh et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, Stiel (forthcoming) finds that municipally owned utilities in Germany perform no better or worse than other organizational forms. Similarly, Bergh et al (forthcoming) analysis of Swedish municipalities suggests that corporatization has no effect on citizen's satisfaction with local public services and may even lead to higher levels of taxes and increased corruption.…”
Section: Current State Of Empirical Researchmentioning
confidence: 97%